2021
DOI: 10.3389/fmed.2020.597791
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of a Clinical Biochemistry-Based Nomogram for Coronavirus Disease 2019

Abstract: Background: This study aimed to explore the predictive value of a clinical biochemistry-based nomogram in COVID-19.Methods: The plasma or serum concentrations/levels of carcinoembryonic antigen (CEA) and other biomarkers, e.g., C-reactive protein (CRP), white blood cell (WBC), interleukin-6 (IL-6), ferritin (Fer), procalcitonin (PCT), lymphocyte percentage (L%), D-dimer (D2), and neutrophils percentage (Neu%), were assessed in 314 hospitalized patients with confirmed COVID-19. The area under the curve was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 21 publications
(13 reference statements)
1
13
0
Order By: Relevance
“…A threshold >1000 ng/mL upon admission was associated with a 18-fold higher in-hospital mortality [ 43 , 45 ]. An increase of neutrophils count was also associated with higher mortality [ 46 , 47 ] and is also usually associated with high D-dimer level with a pro-coagulant state [ 48 , 49 ]. This may support the utility of combining these variables in the assessment of thromboembolic risk.…”
Section: Discussionmentioning
confidence: 99%
“…A threshold >1000 ng/mL upon admission was associated with a 18-fold higher in-hospital mortality [ 43 , 45 ]. An increase of neutrophils count was also associated with higher mortality [ 46 , 47 ] and is also usually associated with high D-dimer level with a pro-coagulant state [ 48 , 49 ]. This may support the utility of combining these variables in the assessment of thromboembolic risk.…”
Section: Discussionmentioning
confidence: 99%
“…In cohort studies of patients without cancer, clinical data shows that up to a quarter of patients with COVID‐19 have elevated CEA values and that the intensity of increase is correlated with severity of COVID‐19. 15 , 16 , 17 , 19 , 20 Among patients hospitalized with COVID‐19, the average CEA value was 8.23 ng/ml, which increased to 14.8 ng/ml among those who died and decreased to 3.8 ng/ml among those who were discharged. 17 Moreover, Chen et al report serial measurement of CEA in 13 patients while they were hospitalized with COVID‐19 and found that levels began to decrease at a median interval of 24 days following infection.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, this work supplements prior research, which identifies a significant increase in tumor markers among non‐cancer patients infected with COVID‐19. 15 , 16 , 17 , 18 , 19 , 20 Despite these clinical observations, the mechanism of benign elevations in tumor markers, like those following COVID‐19 infection, is not known and are hypothesized to stem from the molecular roles of the markers within the pulmonary inflammatory response. 11 , 14 , 17 , 22…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations